Pengaruh Strategi Literasi Berbantuan Model Guided Discovery Learning Terhadap Hasil Belajar Peserta Didik - Yulia Asri Warlinda; Yerimadesi Yerimadesi (Edukimia, 2020)
The basis of research problem is regarding facilities for literacy activities as well selection of learning models that are not appropriate and inadequate. Research conducted using quasi-experimental research methods with a type of randomized control design posttest group only design. Population samples were determined through random sampling techniques. Research measuring tools in the form of cognitive learning test results. Analysis of data concluded that hypothesis was accepted. In other words, application of the literacy strategy assisted by guided discovery learning model has significant effect on learning outcomes.